Kerkregtelike ontwikkelinge in die VGKSA – ’n historiese oorsig (1881-1994) - Van Rooi, L (Nederduitse Gereformeerde Teologiese Tydskrif, 2010)
Church juridical developments in the URCSA – A historical overview (1881-1994) From a church juridical perspective the DRMC and the DRCA took in a necessitated subordinate position in relation to the DRC that has been their self-appointed guardian for the largest part of their histories. As such the autonomy of the DRMC and the DRCA in historical perspective is questionable. However, the indication is that the DRMC and the DRCA underwent certain church juridical developments within their ranks, mostly on the basis of certain ‘freedoms’ allowed by the DRC. As such the synods of the DRMC and the DRCA gradually received more autonomy in making autonomous and authoritative decisions. This gradual process followed the line of amendments to the different constitutions of the DRMC and the DRCA, the ending of the constitutions with their central tenets and the implementation of the different Deeds of Agreement between the DRC and the DRMC and DRCA, as well as the drafting of secondary church orders by the DRMC and the DRCA. As will be pointed out the unification of the DRMC and the DRCA in the formation of the URCSA on the basis of a new and unique church order may indeed be regarded as the culmination of these developments.